2016
DOI: 10.1093/jac/dkw346
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hard cardiovascular events in HIV patients

Abstract: All algorithms showed a modest predictive ability, although the PE and DAD algorithms identified more patients at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
3
32
1
1
Order By: Relevance
“…Other groups very recently investigated the predictive value of Framingham risk score in longitudinal cohorts and reported moderate discrimination ability. Raggi et al [14] from Modena HIV Metabolic Clinic showed a moderate sensitivity (69%) and specificity (72%) of Framingham model and a better prediction of atherosclerotic cardiovascular disease (ASCVD) by pooled cohort equation (PCE) algorithm proposed by American Heart Association [15]. However, the CV event rate in Modena cohort (4/1000 patient-years) was lower compared with our data and could be hypothetically related to a more accurate adherence to preventive CV measure in this HIV Metabolic Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups very recently investigated the predictive value of Framingham risk score in longitudinal cohorts and reported moderate discrimination ability. Raggi et al [14] from Modena HIV Metabolic Clinic showed a moderate sensitivity (69%) and specificity (72%) of Framingham model and a better prediction of atherosclerotic cardiovascular disease (ASCVD) by pooled cohort equation (PCE) algorithm proposed by American Heart Association [15]. However, the CV event rate in Modena cohort (4/1000 patient-years) was lower compared with our data and could be hypothetically related to a more accurate adherence to preventive CV measure in this HIV Metabolic Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have focused on the agreement between predicted risks provided by different algorithms, which varied from poor to excellent [13][14][15][16] , and does not reflect their predictive ability. In contrast, studies which have actually investigated the predictive performance of different algorithms have shown conflicting results 15,[17][18][19][20][21][22][23] . However, these studies were limited by the use of cross-sectional measurements of subclinical CVD endpoints (for which the algorithms were not designed) [24][25][26][27][28] , relatively small sample sizes resulting in a limited number of observed CVD events 17,21,23,25,[27][28][29] , a limited selection of algorithms for comparison [17][18][19][20][21]23,25,29 , and/or by not providing external validation 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated good [ 13 ] versus poor [ 14 ] agreement with the well-established Framingham Risk Score (FRS). The FRS has been reported to accurately predict CVD risk [ 10 , 15 ], underestimate CVD risk [ 12 , 14 ] or overestimate risk [ 15 ]. When applied to HIV cohorts, the HIV-specific CVD risk prediction equation from the Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) cohort has also been noted to both underestimate predicted CVD risk [ 10 , 11 ] and overestimate it [ 15 ] based on expected CVD endpoints.…”
Section: Introductionmentioning
confidence: 99%